Використання соціальних мереж у громадській дипломатії - Сухорольська, Ірина (Видавництво Львівської політехніки, 2014)
The paper addresses the use of social media in public diplomacy. The activity of government structures as well as state officials on the Internet is analyzed.
Keywords: громадська дипломатія; соціальні мережі; віртуальна дипломатія; Web 2.0.